Vocabulary of Emotions in Hagiographies for Children: Functional Aspect - Evgeniya Dmitrieva (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2021)
The article is devoted to the problem of linguistic originality of hagiographic texts for children regarded as a special branch of hagiographic genre, which communicates to the new generation culturally significant senses and values of the ethnic group, with the emphasis on the concept of a religious and moral ideal. The source of the language material was collections of hagiographies for children. The author focuses on lexical units that nominate and describe emotional experiences. The features determining the use of units of this lexical set for the creation of texts that consider children's reading experience are established. It is shown that the specificity of using the vocabulary of emotions in a hagiographic text is determined by its functional load: its usage as a means of characterization (characterological function), the basics of compositional text formation (text-building function), the implementation of the educational orientation of the hagiographic text (didactic function). The vocabulary of emotions is an important means of creating imagery based on metaphorical and metonymic shifts, which contributes to the adaptation of the text to the age and cultural demands of the children's readership. The consideration of functional and stylistic originality of lexemes, their heterogeneity, mixing of bookish and colloquial words has enabled the author to trace transformation processes in hagiographic genre, which are characteristic of modern hagiographic texts.